Bronchial epithelial DNA methyltransferase 3b dampens pulmonary immune responses during Pseudomonas aeruginosa infection - Qin, Wanhai (PLoS Pathog, 2021)
DNA methyltransferase (Dnmt)3b mediates de novo DNA methylation and modulation of Dnmt3b in respiratory epithelial cells has been shown to affect the expression of multiple genes. Respiratory epithelial cells provide a first line of defense against pulmonary pathogens and play a crucial role in the immune response during pneumonia caused by Pseudomonas (P.) aeruginosa, a gram-negative bacterium that expresses flagellin as an important virulence factor. We here sought to determine the role of Dntm3b in respiratory epithelial cells in immune responses elicited by P. aeruginosa. DNMT3B expression was reduced in human bronchial epithelial (BEAS-2B) cells as well as in primary human and mouse bronchial epithelial cells grown in air liquid interface upon exposure to P. aeruginosa (PAK). Dnmt3b deficient human bronchial epithelial (BEAS-2B) cells produced more CXCL1, CXCL8 and CCL20 than control cells when stimulated with PAK, flagellin-deficient PAK (PAKflic) or flagellin. Dnmt3b deficiency reduced DNA methylation at exon 1 of CXCL1 and enhanced NF-ĸB p65 binding to the CXCL1 promoter. Mice with bronchial epithelial Dntm3b deficiency showed increased Cxcl1 mRNA expression in bronchial epithelium and CXCL1 protein release in the airways during pneumonia caused by PAK, which was associated with enhanced neutrophil recruitment and accelerated bacterial clearance; bronchial epithelial Dnmt3b deficiency did not modify responses during pneumonia caused by PAKflic or Klebsiella pneumoniae (an un-flagellated gram-negative bacterium). Dnmt3b deficiency in type II alveolar epithelial cells did not affect mouse pulmonary defense against PAK infection. These results suggest that bronchial epithelial Dnmt3b impairs host defense during Pseudomonas induced pneumonia, at least in part, by dampening mucosal responses to flagellin.